Occupational health and safety management systems – analysis of selected requirements for evaluation of occupational health and safety performance - Marcin Krause; Szymon Salomon (Zarządzanie Innowacyjne w Gospodarce i Biznesie)
The publication undertakes the problems of occupational health and safety in the aspect of requirements for occupational health and safety management systems. The aim of the work was analysis of selected aspects of evaluation of occupational health and safety performance according to the ISO 45001:2018 standard. Performance evaluation and improvement are one of the basic requirements, that determine the suitability, adequacy, effectiveness and efficiency of management systems. The essential element of the study was the development of assumptions for evaluation of occupational health and safety performance, which include the analysis of occupational health and safety state and the evaluation of occupational health and safety management systems.